Informed Health Choices media intervention for improving people's ability to critically appraise the trustworthiness of claims about treatment effects: a mixed-methods process evaluation of a randomised trial in Uganda. Issue 12 (17th December 2019) - Semakula, Daniel; Nsangi, Allen; Oxman, Andrew; Glenton, Claire; Lewin, Simon; Rosenbaum, Sarah; Oxman, Matt; Kaseje, Margaret; Austvoll-Dahlgren, Astrid; Rose, Christopher James; Fretheim, Atle; Sewankambo, Nelson
Abstract : We developed the Informed Health Choices podcast to improve people's ability to assess claims about the effects of treatments. We evaluated the effects of the podcast in a randomised trial. Objectives: We conducted this process evaluation to assess the fidelity of the intervention, identify factors that affected the implementation and impact of the intervention and could affect scaling up, and identify potential adverse and beneficial effects. Setting: The study was conducted in central Uganda in rural, periurban and urban settings. Participants: We collected data on parents who were in the intervention arm of the Informed Health Choices study that evaluated an intervention to improve parents' ability to assess treatment effects. Procedures: We conducted 84 semistructured interviews during the intervention, 19 in-depth interviews shortly after, two focus group discussions with parents, one focus group discussion with research assistants and two in-depth interviews with the principal investigators. We used framework analysis to manage qualitative data, assessed the certainty of the findings using the GRADE-CERQual (Grading of Recommendations, Assessment, Development and Evaluations-Confidence in the Evidence from Reviews of Qualitative Research) approach, and organised findings in a logic model. Outcomes: Proportion of participants listening to all episodes; factors influencing the implementation of the podcast; ways to scale up and any adverse and beneficial effects. Results: All participants who completed the study listened to the podcast as intended, perhaps because of the explanatory design and recruitment of parents with a positive attitude. This was also likely facilitated by the podcast being delivered by research assistants, and providing the participants with MP3 players. The podcast was reportedly clear, understandable, credible and entertaining, which motivated them to listen and eased implementation. No additional adverse effects were reported. Conclusions: Participants experienced the podcast positively and were motivated to engage with it. These findings help to explain the short-term effectiveness of the intervention, but not the decrease in effectiveness over the following year.